Hafnium inspired activation of highly hindered anhydrides in the acylation of alcohols and polyols. Issue 12 (21st March 2018) - Mensah, Enoch; Day, Aaron; Thomas, Raven
Graphical abstract: Highlights: A highly efficient method for activating highly hindered acid anhydrides has been developed. The method relies on the capacity of the hafnium species to activate hindered acid anhydrides to protect hydroxyl groups. The method has wide substrate scope to afford ester products in good to excellent yields. Abstract: A novel and highly efficient method for activating highly hindered acid anhydrides towards the acylation of alcohols and carbohydrate-derived polyols has been developed. This new method relies on the capacity of the hafnium triflate catalyst Hf(OTf)2 to activate highly hindered acid anhydrides, and to direct the acylation reaction. This new acylation protocol is mild and proceed at room temperature with low catalyst loading. The method is versatile and has been extended to different alcohol substrates with different steric encumbrance as well as carbohydrate-derived polyols to afford the corresponding ester products in good to excellent yields.